Modified expression for calculating refractive index of ANB8-N type binary semiconductors - Latreche, Abdelhakim; Daoud, Salah (International Journal of Physical Research, 2016)
In their recent work, Bahadur and Mishra proposed a new simple formula between the high-frequency refractive index and optical elec-tronegativity difference, which has been established for large number of ANB8-N type binary semiconductors (groups: I-VII, II-VI, III-V and IV-VI.). In the present work, we have improved their expression by addition a correction term in their proposed formula. The minimum average percentage deviation in the present approach reveals that the modified Bahadur relation proves its identity and soundness compared to that of Bahadur’s and others authors' relations.